Multichannel ballistocardiography: A comparative analysis of heartbeat detection across different body locations - Ladrova, Martina; Barvik, Filip; Brablik, Jindrich; Jaros, Rene; Martinek, Radek (PloS one, 2024)
The paper presents a validation of novel multichannel ballistocardiography (BCG) measuring system, enabling heartbeat detection from information about movements during myocardial contraction and dilatation of arteries due to blood expulsion. The proposed methology includes novel sensory system and signal processing procedure based on Wavelet transform and Hilbert transform. Because there are no existing recommendations for BCG sensor placement, the study focuses on investigation of BCG signal quality measured from eight different locations within the subject's body. The analysis of BCG signals is primarily based on heart rate (HR) calculation, for which a J-wave detection based on decision-making processes was used. Evaluation of the proposed system was made by comparing with electrocardiography (ECG) as a gold standard, when the averaged signal from all sensors reached HR detection sensitivity higher than 95% and two sensors showed a significant difference from ECG measurement.
Keywords: balistokardiografie; lidé; Ballistocardiography; Adult; Female; elektrokardiografie; Humans; vlnková analýza; Signal Processing, Computer-Assisted; počítačové zpracování signálu; mužské pohlaví; mladý dospělý; Wavelet Analysis; Electrocardiography; srdeční frekvence; ženské pohlaví; Young Adult; Male; dospělí; Heart Rate